Directed Evolution of Enzymes for Industrial Biocatalysis. Issue 3 (10th December 2015) - Porter, Joanne L.; Rusli, Rukhairul A.; Ollis, David L.
Abstract: Enzymes have the potential to catalyse a wide variety of chemical reactions. They are increasingly being sought as environmentally friendly and cost‐effective alternatives to conventional catalysts used in industries ranging from bioremediation to applications in medicine and pharmaceutics. Despite the benefits, they are not without their limitations. Many naturally occurring enzymes are not suitable for use outside of their native cellular environments. However, protein engineering can be used to generate enzymes tailored for specific industrial applications. Directed evolution is particularly useful and can be employed even when lack of structural information impedes the use of rational design. The aim of this review is to provide an overview of current industrial applications of enzyme technology and to show how directed evolution can be used to modify and to enhance enzyme properties. This includes a brief discussion on library generation and a more detailed focus on library screening methods, which are critical to any directed evolution experiment. Abstract : Engineering of tailored biocatalysts : Enzymatic methods offer an environmentally friendly alternative to many current industrial catalysts and reagents. The field of directed evolution is continually advancing to facilitate the generation of biocatalysts capable of increasingly ambitious biotransformations.